Disney Descendants : 2 movie collection [videorecording (DVD)] : Descendants ; Descendants 2 - Parriott, Sara; McGibbon, Josann; Cameron, Dove; Boyce, Cameron; Carson, Sofia; Stewart, Boo Boo; Hope, Mitchell, 1994-; D'Amico, Brenna, 2000-; Paxson, Melanie; Chenoweth, Kristin; McClain, China Anne (Disney DVD., 2018)
Descendants: A present-day idyllic kingdom where the benevolent teenage son of King Adam and Queen Belle offers a chance of redemption for the trouble making offspring of Disney's classic villains: Cruella De Vil (Carlos), Maleficent (Mal), the Evil Queen (Evie) and Jafar (Jay).